Prostatic diseases: is it toxic or genetic? Study of TNF alpha gene polymorphism and cigarette smoking in cases of prostate cancer and benign prostatic hyperplasia - M. Attalla, Sohayla; Housen, Maha; El-Samanoudy, Ayman Z.; Abdalla, Hussein A. (Malaysian Society of Applied Biology, 2016)
Inflammation has been implicated as an etiological factor, in several human cancers. Allelic variants of the genes involved in inflammatory pathways are logical candidates as genetic determinants of prostate cancer risk. Besides genetic factors, environmental factors such as smoking are an important risk factor for prostate cancer. This study aimed to investigate whether 308 G/A single nucleotide polymorphism of tumor necrosis factor-α (TNF-α) gene promoter region was associated with outcomes of prostate cancer and to analyze the gene environment interaction between 308 G/A TNF polymorphism and cigarette smoking. A total of 282 patients with prostate cancer (143 smokers, 139 non smoker) and 212 patients with benign prostatic hyperplasia (105 smokers, 107 non smokers) along with 115 healthy control were enrolled in the study. Urinary Cotinine and serum TNF and PSA levels were measured using ELISA technique. TNF genotyping was performed using PCR-RFLP technique. Prostate cancer was significantly associated with TNF G/G genotype and this is accompanied by elevated plasma TNF, PSA and urinary Cotinine. Cancer smokers showed a high frequency of TNF-α 308 G allele compared with other patient groups associated with increased TNF levels. Results of this study support the hypothesis that polymorphism in proinflammatory genes may be important in prostate cancer development and the sequence variants in these inflammatory genes may interact with environmental modifiers such as cigarette smoking to increase prostate cancer risk.